Pengambilan Keputusan Melalui Strategi Komunikasi Efektif pada Keluarga Pasien Kritis - Suhartini, Suhartini; Lahati, Nurul Safira; Anggorowati, Anggorowati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine effective communication strategies with the families of patients receiving treatment in the ICU. The method used is a scoping review using Arksey and O'Malley model analysis. A systematic search was carried out using database bases, namely Sciencedirect, Scopus, Proquest. The research results show that there are three categories, namely family-centered care, special aspects of communication and structured family communication guidelines. In conclusion, an effective communication approach with family members in the Intensive Care Unit provides a very important role for critical patient-centered care in the intensive care unit. Keywords: Intensive Care Unit, Family, Communication